Process Hazard Management System (PROHAMS) based on PSM - Azmi , Mohd Shariff; Hanida, Abdul Aziz; Yew, Kwang Hooi (2014)
The key contributing factors that could prevent major accidents, injuries and fatalities in the process industries are by controlling the process hazards within the process plant. However, accidents can still happen if the process hazards are inadequately managed. One of the established standards to manage process hazards is Process Hazard Analysis (PHA) of Process Safety Management (PSM) 29 CFR 1910.119(e). This paper presents a PHA management and implementation technique that could fulfil the 29 CFR 1910.119(e) requirements. The technique provides organized strategies to manage and track information, documents, and resolution of recommendations related to the process hazards. Piping and Instrumentation Diagram (P&ID) is used as a foundation for the PHA data management. The data is efficiently managed using a computer database prototype known as Process Hazards Management System (PROHAMS). Implementation of this technique could help the employers to manage process hazards successfully and compliance with PSM regulation.